2015
DOI: 10.3390/ijms16034615
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Biomimetic Remineralization of Human Dentine: A Systematic Review

Abstract: This study aimed to review the laboratory methods on biomimetic remineralization of demineralized human dentine. A systematic search of the publications in the PubMed, TRIP, and Web of Science databases was performed. Titles and abstracts of initially identified publications were screened. Clinical trials, reviews, non-English articles, resin-dentine interface studies, hybrid layer studies, hybrid scaffolds studies, and irrelevant studies were excluded. The remaining papers were retrieved with full texts. Manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 51 publications
(135 reference statements)
1
112
0
5
Order By: Relevance
“…For example, phosphorylated chitosan effectively complexes Ca 2+ to enhance tooth enamel remineralization and prevent future acid-catalyzed demineralization. 26,41 We examined the Ca 2+ chelation properties of P-chitosan by measuring total calcium chelation as a function of phosphorylation degree (Table 3). P-chitosan chelation was compared to that observed from control chitosan (i.e., no phosphorylation).…”
Section: Resultsmentioning
confidence: 99%
“…For example, phosphorylated chitosan effectively complexes Ca 2+ to enhance tooth enamel remineralization and prevent future acid-catalyzed demineralization. 26,41 We examined the Ca 2+ chelation properties of P-chitosan by measuring total calcium chelation as a function of phosphorylation degree (Table 3). P-chitosan chelation was compared to that observed from control chitosan (i.e., no phosphorylation).…”
Section: Resultsmentioning
confidence: 99%
“…Healthy 44%) - it became apparent that effective dentin remineralization (determined on the basis of mechanical recovery) was only possible if both the extrafibrillar and intrafibrillar mineral components were replenished, (Figure 1) a conjecture that is largely supported today. Consequently, several strategies to remineralize dentin proposed to date highlight the importance of recovering the intrafibrillar mineral of demineralized (and carious) dentin (see 40, 41 for recent reviews), a process that has also been called functional remineralization, biomimetic remineralization, hierarchical remineralization and other similar terms. Similarly, these studies contributed to the development of numerous novel strategies that seek to prevent degradation of dentin-adhesive interfaces 41 , of scaffold materials with improved biological and physical properties 42 , and even the treatment of disease conditions such as DI-II-like dentin (Dspp knockout mice) 43 .…”
Section: Dentin Inorganic Content – Extrafibrillar and Intrafibrilmentioning
confidence: 99%
“…Later studies has revealed that carious dentin display four different zones, each zone with distinct microstructure changes, nanomechanical properties and decreasing mineral contents [46]. Efforts to achieve biomimetic remineralization in dentin are ongoing [47], with a major rationale that once the dentin begins to remineralize its biomechanical properties improve [48]. However, the remineralisation of these zones in the dentin is far more complex than in enamel, since there are no seed mineral crystals that remain like in enamel [49].…”
Section: Restorative Materials and The Tooth-restoration Interfacementioning
confidence: 99%